Adaptation of world experience of crisis management in Ukraine - Храпкіна, Валентина Валентинівна; Чучко, Олена Петрівна (Technology audit and production reserves, 2015)
The forms of anti-crisis management in countries with developed market economics are revealed in the article. In most countries it is realized through legislation improvement in the field of employment, increase the number of jobs, especially for young people, coordinating the efforts of various government departments to develop and conduct of economic policy through increase a state intervention in the economy. It is established that in direction of anti-crisis management in Europe prevails selective approach aimed at stimulation of specific companies; priorities of state sector in Scandinavia are education, health care, pension and labor market. In addition, in some countries to find innovative structures of enterprises, increase their competitiveness and efficiency of recovery used developing programs of privatization that have their own characteristics in each country. The generalization of the world experience of solving the problems of bankruptcy of enterprises made it possible to distinguish two approaches to this problem. The first is a liquidation of the company, the second is the reorganization. It should be emphasized on dominance of the second approach. Worldwide anti-crisis management models provide different potential for progressive social and economic progress. Usage of positive experience should be the first step in reforming the system of anti-crisis management.